Hemizygous mutations in SNAP29 unmask autosomal recessive conditions and contribute to atypical findings in patients with 22q11.2DS. Issue 2 (11th December 2012) - McDonald-McGinn, Donna M; Fahiminiya, Somayyeh; Revil, Timothée; Nowakowska, Beata A; Suhl, Joshua; Bailey, Alice; Mlynarski, Elisabeth; Lynch, David R; Yan, Albert C; Bilaniuk, Larissa T; Sullivan, Kathleen E; Warren, Stephen T; et al.
Abstract : Background: 22q11.2 deletion syndrome (22q11.2DS) is the most common microdeletion disorder, affecting an estimated 1 : 2000–4000 live births. Patients with 22q11.2DS have a broad spectrum of phenotypic abnormalities which generally includes congenital cardiac abnormalities, palatal anomalies, and immunodeficiency. Additional findings, such as skeletal anomalies and autoimmune disorders, can confer significant morbidity in a subset of patients. 22q11.2DS is a contiguous gene DS and over 40 genes are deleted in patients; thus deletion of several genes within this region contributes to the clinical features. Mutations outside or on the remaining 22q11.2 allele are also known to modify the phenotype. Methods: We utilised whole exome, targeted exome and/or Sanger sequencing to examine the genome of 17 patients with 22q11.2 deletions and phenotypic features found in <10% of affected individuals. Results and conclusions: In four unrelated patients, we identified three novel mutations in SNAP29, the gene implicated in the autosomal recessive condition cerebral dysgenesis, neuropathy, ichthyosis and keratoderma (CEDNIK). SNAP29 maps to 22q11.2 and encodes a soluble SNARE protein that is predicted to mediate vesicle fusion at the endoplasmic reticulum or Golgi membranes. This work confirms that the phenotypic variability observed in a subset of patients with 22q11.2DS is due to mutations on the non-deleted chromosome, which leads to unmasking of autosomal recessive conditions such as CEDNIK, Kousseff, and a potentially autosomal recessive form of Opitz G/BBB syndrome. Furthermore, our work implicates SNAP29 as a major modifier of variable expressivity in 22q11.2 DS patients.